Investigating the Motivations Behind users' Photo Sharing on Social Media (London Journal of Research In Management & Business, 2024)
Social media platforms have transformed communication and interaction, leading to the trend of photo posting. This paper aims to develop and validate a research model examining the factors influencing user intention to post photos on social media and its impact on social commerce.This study integrates media functions and social processes to create a comprehensive research model, exploring social presence, media richness, use and gratification, self-disclosure, and boast motive as key elements shaping user behavior on social media.Data was collected through a survey of social media platform users to measure the constructs within the research model. Data analysis was conducted using SmartPLS to validate the model and examine relationships between the constructs.The study provided empirical evidence supporting the research model, highlighting the significant influence of social presence, media richness, use and gratification, self-disclosure, and boast motive on photo posting intention.The study offers insights for e-commerce and social media research, guiding effective marketing strategies and user engagement tactics. It also provides social media managers and marketers a framework to enhance user engagement and loyalty by understanding user motivations and preferences.
Keywords: Institutional Evaluation. Strategic Anticipation. Higher Education; Civilisations; performance; nepotism; sociometry; culture.; ocial media; Photo posting; Social commerce